Differential contributions of ApoE4 and female sex to BACE1 activity and expression mediate Aβ deposition and learning and memory in mouse models of Alzheimer’s disease - Hou, Xu; Adeosun, Samuel O.; Zhang, Qinli; Barlow, Brett; Brents, Melissa; Zheng, Baoying; Wang, Junming (Frontiers in Aging Neuroscience, 2015)
Alzheimer’s disease (AD), the most common form of dementia, disproportionately affects women in both prevalence and severity. This increased vulnerability to AD in women is strongly associated with age-related ovarian hormone loss and apolipoprotein E 4 allele (ApoE4), the most important genetic risk factor for sporadic AD. Up to date, the mechanism involved in the interaction between ApoE4 and sex/gender in AD is still unclear. This study evaluated the sex-dependent ApoE4 effects on learning and memory, Aβ deposition and potential mechanisms, using mice bearing both sporadic (ApoE4) and familial (APPSwe, PS1M146V, tauP301L; 3xTg) AD risk factors and compared with sex- and age-matched 3xTg or nonTg mice. Compared to nonTg mice, transgenic mice of both sexes showed spatial learning and memory deficits in the radial arm water maze and novel arm discrimination tests at 20 months of age. However, at 10 months, only ApoE4/3xTg mice showed significant learning and memory impairment. Moreover, molecular studies of hippocampal tissue revealed significantly higher protein levels of Aβ species, β-site APP cleavage enzyme (BACE1) and Sp1, a transcription factor of BACE1, in female ApoE4/3xTg when compared with female nonTg, female 3xTg and male ApoE4/3xTg mice. Significantly increased BACE1 enzymatic activities were observed in both male and female mice carrying ApoE4; however, only the females showed significant higher BACE1 expressions. Together, these data suggest that ApoE4 allele is associated with increased BACE1 enzymatic activity, while female sex plays an important role in increasing BACE1 expression. The combination of both provides a molecular basis for high Aβ pathology and the resultant hippocampus-dependent learning and memory deficits in female ApoE4 carriers.